At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Let's solve the equation [tex]\(\sqrt{x + 10} - 1 = x\)[/tex] step-by-step.
1. Isolate the square root term:
Start by adding 1 to both sides of the equation:
[tex]\[ \sqrt{x + 10} = x + 1 \][/tex]
2. Square both sides:
To eliminate the square root, square both sides of the equation:
[tex]\[ (\sqrt{x + 10})^2 = (x + 1)^2 \][/tex]
This simplifies to:
[tex]\[ x + 10 = (x + 1)^2 \][/tex]
3. Expand the right side:
Expand [tex]\((x + 1)^2\)[/tex]:
[tex]\[ x + 10 = x^2 + 2x + 1 \][/tex]
4. Rearrange the equation:
Finally, move all terms to one side to form a standard quadratic equation:
[tex]\[ x + 10 = x^2 + 2x + 1 \][/tex]
Subtract [tex]\(x + 10\)[/tex] from both sides:
[tex]\[ 0 = x^2 + x - 9 \][/tex]
Therefore, the equation [tex]\(\sqrt{x + 10} - 1 = x\)[/tex] simplifies to [tex]\(x + 10 = x^2 + 2x + 1\)[/tex].
Thus, the second equation, [tex]\(x+10 = x^2 + 2x + 1\)[/tex], is the one that matches the transformed form of [tex]\(\sqrt{x + 10} - 1 = x\)[/tex].
1. Isolate the square root term:
Start by adding 1 to both sides of the equation:
[tex]\[ \sqrt{x + 10} = x + 1 \][/tex]
2. Square both sides:
To eliminate the square root, square both sides of the equation:
[tex]\[ (\sqrt{x + 10})^2 = (x + 1)^2 \][/tex]
This simplifies to:
[tex]\[ x + 10 = (x + 1)^2 \][/tex]
3. Expand the right side:
Expand [tex]\((x + 1)^2\)[/tex]:
[tex]\[ x + 10 = x^2 + 2x + 1 \][/tex]
4. Rearrange the equation:
Finally, move all terms to one side to form a standard quadratic equation:
[tex]\[ x + 10 = x^2 + 2x + 1 \][/tex]
Subtract [tex]\(x + 10\)[/tex] from both sides:
[tex]\[ 0 = x^2 + x - 9 \][/tex]
Therefore, the equation [tex]\(\sqrt{x + 10} - 1 = x\)[/tex] simplifies to [tex]\(x + 10 = x^2 + 2x + 1\)[/tex].
Thus, the second equation, [tex]\(x+10 = x^2 + 2x + 1\)[/tex], is the one that matches the transformed form of [tex]\(\sqrt{x + 10} - 1 = x\)[/tex].
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.